(untitled) (London Journal of Medical and Health Research, 2024)
The quality of higher education is a topic of great relevance, as it is directly linked to the formation of qualified professionals for the exercise of their roles. To assess the quality of higher education, the Ministry of Education established parameters and implemented various evaluation instruments. The publication of Law 10.861/2004 systematized these assessments, highlighting the need for an in-depth study of the system and the active participation of the academic community in this process. The specific objective was to apply new evaluation instruments following a motivation and awareness campaign, assessing the new participation rates. The research was qualitative and quantitative, using a case study with document analysis. In the data discussion analysis, a comparative method was used to address the specific objective. The legislation from INEP and MEC provided the theoretical foundation for this investigation. In the final considerations, it was found that continuous mobilization and awareness efforts, through effective campaigns, enhance the understanding of the topic and contribute to improving the teaching and learning process, as well as promoting improvements in institutional infrastructure.